A Prospective Observational Study on Multiplate®-, ROTEM®- and Thrombin Generation Examinations Before and Early After Implantation of a Left Ventricular Assist Device (LVAD) - Opfermann, Philipp; Felli, Alessia; Schlömmer, Christine; Dworschak, Martin; Bevilacqua, Michele; Mouhieddine, Mohamed; Zimpfer, Daniel; Zuckermann, Andreas; Steinlechner, Barbara (Frontiers in Medicine, 2022)
Background: Heart failure patients are frequently on coagulation-active medications before LVAD implantation and perioperative bleeding is a frequent complication after left ventricular assist device (LVAD) implantation. The role of point-of-care coagulation tests in assessing bleeding risk for LVAD implantation and early postoperative course is not well established. Methods: We prospectively enrolled 25 patients with terminal heart failure undergoing LVAD implantation. We examined if preoperative TRAP-, ASPI- and ADP- test of Multiplate® platelet aggregometry, ROTEM® rotational thromboelastometry (INTEM, EXTEM, FIBTEM) and thrombin generation assay are correlated with estimated total blood loss (primary outcome parameter) during the first 21 days after LVAD implantation and compared the baseline values of these measurements between patients with a bleeding event(s) to those without. Results: 7 out of 25 (28%) patients experienced a bleeding event of which 4 required a surgical revision. Of the preoperatively performed measurements the TRAP test (Spearman’s Rho (ρ) = - 0.5, p = 0.01), INTEM CFT (ρ = 0.72, p < 0.001), INTEM alpha (- 0.7, p < 0.001), EXTEM MCF (ρ = - 0.63; p < 0.001), EXTEM alpha (ρ = - 0.67; p < 0.001), FIBTEM MCF (ρ = - 0.41; p = 0.042), Fibrinogen (Clauss) (ρ = - 0.5; p = 0.011), Anti-thrombin III activity (ρ = - 0.49; p = 0.013) and platelet count (ρ = - 0.42; p = 0.034) were significantly correlated to total blood loss. Patients undergoing a surgical bleeding revision had significantly reduced values in TRAP- (31.5 IQR (17.25-43.5U) vs. 69 IQR (52.5-87U); p = 0.004), ASPI- (16.5 IQR (5.5-35.7U) vs. 39 IQR (24.5-62.5U); p = 0.038), ADP- (30 IQR (22-69U) vs. 12.5 IQR (8.7-21.5U); p = 0.01), EXTEM MCF- (63 IQR (57.7-63.7) vs. 67 IQR (65-75.5); p = 0.019) and EXTEM alpha (74 IQR (68.75-74) vs. 79 IQR (78-80.5); p = 0.002) values employed before LVAD implantation. Conclusion: Multiplate® and ROTEM® used before LVAD implantation may identify LVAD candidates with platelet dysfunction and alterations of the primary hemostasis and could guide anesthetists and intensive care practitioners in bleeding risk stratification and in the perioperative clinical management.